Measuring The Regulations of Islamic Philanthropic Institutions in Community Welfare Programs - Sunardi, Dedi; Aufa, Maya (MUAMALATUNA, 2025)
This article aims to describe the implementation of the regulations of Islamic Philanthropic institutions, namely the practice of social activities by giving and sharing voluntarily with the aim of welfare and social justice based on the principles of Islamic teachings. So that a standard concept for the implementation of rules was found that could be used as a key factor in creating welfare and justice in accordance with Islamic principles. The fact that the growth and development of Islamic philanthropic institutions in carrying out community welfare programs is growing rapidly, one of which is in Banten Province, on the grounds that the poverty rate is quite significant. Using an empirical juridical method with descriptive analysis techniques, using Islamic devotional theory to answer research problems. Islamic philanthropic institutions such as Baznas, Dompet Dhuafa and similar institutions in Banten have met accountability standards, but due to limited literacy to local needs and community involvement, the programs implemented are not in accordance with the basic needs of the community. The absence of regulations on Islamic philanthropic institutions causes the assessment of social welfare achievements to be immeasurable.